IT implementation and customer results: the mediating role of the competitive priorities achieved by the firm. (14th August 2019) - Haro, Manuel Rios De; Opazo-Basáez, Marco; Aranda, Daniel Arias
Studies in information technology (IT) increasingly focus on key variables that might explain the effect of the implementation of IT strategic tools on business performance. In the search to uncover how to achieve greater performance, this study examines how IT implementation, measured through IT use and IT integration, affects the competitive priorities achieved by the firm and customers' results. To do so, an analysis of these interactions is carried out applying the structural equation modelling (SEM) methodology to a survey on Spanish manufacturing firms. The results show a significant and positive relationship between IT implementation and competitive priorities related to the flexibility observed, innovation developed, and delivery time needed. The study also notes that IT integration is positively and directly related to customer results, whereas the relationship between IT use and customer results is positively but indirectly related to those customer results, with the competitive priorities achieved by the firm acting as mediators in this relationship. The main conclusions deriving from the present study clarify the role of IT implementation in organisations, highlighting the role of previous competitive priorities as being responsible for the success of IT implementation.